A modified waste fiber and its preparation method and application

By treating the copper clad waste into modified waste fibers and applying them to fiber-reinforced resin composites, the problem of high cost of glass fibers is solved, and the effect of reducing costs and increasing tensile strength is achieved.

CN115961471BActive Publication Date: 2025-04-01JIANGXI GUANGYUAN CHEM +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310084718.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-08
Publication Date
2025-04-01
Estimated Expiration
2043-02-08

AI Technical Summary

Technical Problem

The glass fiber used in existing fiber-reinforced resin composite materials is costly and difficult to effectively reduce.

Method used

Modified waste fibers are prepared by treating the copper clad waste material into waste fibers, coated with calcium silicate sol, calcined into wollastonite, and then treated with a modifier. This method not only reduces the cost of the fiber, but also improves the compatibility and tensile strength of the fiber with the resin.

Benefits of technology

The cost of fiber-reinforced resin composites is achieved, while improving its tensile strength, achieving similar properties to glass fibers.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of waste fiber recycling, and provides a modified waste fiber and a preparation method and application thereof. The preparation method of the present invention uses one or more of concentrated sulfuric acid, concentrated nitric acid, concentrated hydrochloric acid, hydrofluoric acid and concentrated phosphoric acid as a corrosive liquid, which can completely dissolve and remove the solidified resin and copper foil in the copper-clad laminate waste, obtain waste fibers with clean surfaces, and then use calcium silicate sol to infiltrate the waste fibers, so that calcium silicate whiskers grow in situ on the surface of the waste fibers, thereby increasing the specific surface area of ​​the waste fibers; wollastonite-coated waste fibers are then treated with a modifier, thereby improving the compatibility of the waste fibers with the resin glue, thereby improving the tensile strength of the resin-based composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste fiber recycling, and in particular to a modified waste fiber and a preparation method and application thereof. Background Art

[0002] Fiber-reinforced resin composites manufactured by sheet molding compound (SMC) and paste molding compound (BMC) processes are low-end products and costs must be strictly controlled.

[0003] At present, the commonly used reinforcing material in fiber-reinforced resin composite materials is glass fiber, but the price of glass fiber purchased directly from the market is expensive. If it is necessary to further reduce the cost of glass fiber reinforced resin composite materials, it can be regulated from the source of the fiber.

[0004] The circuit board industry produces tens of thousands of tons of copper clad laminate waste every year (copper clad laminate is a product made of wood pulp paper or glass fiber as reinforcing materials, impregnated with resin, covered with copper foil on one or both sides, and hot pressed). If these copper clad laminate wastes are processed into waste fibers and replaced with waste fibers in composite products, costs can be greatly reduced. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a modified waste fiber and a preparation method and application thereof. The modified waste fiber obtained by the preparation method provided by the present invention has low cost and can improve the tensile strength of resin-based composite materials.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing modified waste fiber, comprising the following steps:

[0008] The waste copper clad laminate is immersed in a corrosive solution to dissolve the waste copper clad laminate to obtain waste fibers;

[0009] The silicate ester and the acid solution are mixed and hydrolyzed to obtain silica sol;

[0010] mixing the silica sol and a soluble calcium salt to obtain a calcium silicate sol;

[0011] impregnating the waste fiber in the calcium silicate sol to obtain waste fiber coated with the calcium silicate sol;

[0012] calcining the waste fiber coated with the calcium silicate sol to obtain wollastonite coated waste fiber;

[0013] impregnating the wollastonite-coated waste fiber with a modifier to obtain the modified waste fiber;

[0014] The etching solution includes one or more of concentrated sulfuric acid, concentrated nitric acid, concentrated hydrochloric acid, hydrofluoric acid and concentrated phosphoric acid.

[0015] Preferably, the silicate comprises one or more of methyl orthosilicate, ethyl orthosilicate, isopropyl silicate and butyl silicate;

[0016] The acid solution includes hydrochloric acid aqueous solution, sulfuric acid aqueous solution, nitric acid aqueous solution or acetic acid aqueous solution; the mass concentration of the acid solution is 10-30%.

[0017] Preferably, the molar ratio of the silica sol to the soluble calcium salt is 1:1 based on silicate; the silica sol and the soluble calcium salt are mixed at room temperature for 10 to 120 minutes.

[0018] Preferably, the immersion time is 10 to 48 hours.

[0019] Preferably, the calcination temperature is 500-800° C., and the holding time is 3-5 hours.

[0020] Preferably, the modifier is a lipophilic active agent, and the lipophilic modifier includes one or more of a silane coupling agent, a phthalate coupling agent, organic silicon, stearic acid and a phosphate ester.

[0021] Preferably, the mass of the modifier is 1-3% of the mass of the waste fiber; the soaking temperature is 20-80° C., and the soaking time is 3-8 hours.

[0022] The present invention also provides modified waste fibers obtained by the preparation method described in the above technical solution.

[0023] The present invention also provides a molding compound, comprising resin, fiber and calcium carbonate;

[0024] The mass ratio of the resin, fiber and calcium carbonate is 100:20-35:70-80;

[0025] The fiber is the modified waste fiber described in the above technical solution.

[0026] The present invention also provides a fiber-reinforced resin-based composite material, which is obtained by arranging the plastics described in the above technical solution layer by layer and then curing them.

[0027] The present invention provides a method for preparing modified waste fiber, comprising the following steps: soaking copper clad laminate waste in an etching solution to dissolve it and obtain waste fiber; mixing silicate and acid solution to hydrolyze it to obtain silica sol; mixing the silica sol with a soluble calcium salt to obtain calcium silicate sol; soaking the waste fiber in the calcium silicate sol to obtain waste fiber coated with the calcium silicate sol; calcining the waste fiber coated with the calcium silicate sol to obtain wollastonite-coated waste fiber; soaking the wollastonite-coated waste fiber with a modifier to obtain the modified waste fiber; the etching solution includes one or more of concentrated sulfuric acid, concentrated nitric acid, concentrated hydrochloric acid, hydrofluoric acid and concentrated phosphoric acid. The preparation method provided by the present invention uses one or more of concentrated sulfuric acid, concentrated nitric acid, concentrated hydrochloric acid, hydrofluoric acid and concentrated phosphoric acid as etching solution, which can completely dissolve and remove the solidified resin and copper foil in the copper clad laminate waste to obtain waste fiber with a clean surface; and the present invention uses copper clad laminate waste to prepare waste fiber as a resin-based reinforcing material, thereby reducing the cost of resin-based composite materials. At the same time, the present invention utilizes calcium silicate sol to infiltrate waste fibers, so that calcium silicate whiskers grow in situ on the surface of the waste fibers, thereby increasing the specific surface area of ​​the waste fibers and improving the tensile strength of the resin-based composite material; wollastonite-coated waste fibers are then treated with a modifier, which also improves the compatibility of the waste fibers with the resin glue, thereby improving the tensile strength of the resin-based composite material.

[0028] The present invention also provides the modified waste fiber obtained by the preparation method described in the above technical solution. The modified waste fiber provided by the present invention has good compatibility with the resin glue, and improves the tensile strength of the resin-based composite material.

[0029] The present invention also provides a molding compound, comprising resin, fiber and calcium carbonate; the mass ratio of the resin, fiber and calcium carbonate is 100:20-35:70-80; the fiber is the modified waste fiber described in the above technical solution. Since the molding compound provided by the present invention uses the modified waste fiber, the cost of the molding compound is reduced while the tensile strength of the resin-based composite material is improved.

[0030] The present invention also provides a fiber-reinforced resin-based composite material, which is obtained by curing the molding compound described in the above technical solution. Since the fiber-reinforced resin-based composite material provided by the present invention uses modified waste fibers, the cost of the fiber-reinforced resin-based composite material is reduced while the tensile strength of the resin-based composite material is improved. DETAILED DESCRIPTION

[0031] The present invention provides a method for preparing modifier-coated wollastonite modified fiber, comprising the following steps:

[0032] The waste copper clad laminate is immersed in a corrosive solution to dissolve the waste copper clad laminate to obtain waste fibers;

[0033] The silicate ester and the acid solution are mixed and hydrolyzed to obtain silica sol;

[0034] mixing the silica sol and a soluble calcium salt to obtain a calcium silicate sol;

[0035] impregnating the waste fiber in the calcium silicate sol to obtain waste fiber coated with the calcium silicate sol;

[0036] calcining the waste fiber coated with the calcium silicate sol to obtain wollastonite coated waste fiber;

[0037] impregnating the wollastonite-coated waste fiber with a modifier to obtain the modified waste fiber;

[0038] The etching solution includes one or more of concentrated sulfuric acid, concentrated nitric acid, concentrated hydrochloric acid, hydrofluoric acid and concentrated phosphoric acid.

[0039] In the present invention, unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.

[0040] The invention soaks the waste copper clad plate in a corrosive liquid to dissolve the waste copper clad plate and obtain the waste fiber.

[0041] In the present invention, the etching solution includes one or more of concentrated sulfuric acid, concentrated nitric acid, concentrated hydrochloric acid, hydrofluoric acid and concentrated phosphoric acid, and is more preferably concentrated nitric acid. In the present invention, the concentration of the etching solution is preferably 10-20 mol / L, and is more preferably 12 mol / L. In the present invention, the dissolution temperature is preferably room temperature, that is, no additional cooling or heating is required. In the present invention, the dissolution time is preferably 24-48 hours.

[0042] After the dissolution, the present invention preferably further comprises washing, cutting and drying the obtained loose fibers in sequence. In the present invention, the washing agent preferably comprises water; the present invention does not specifically limit the number of washings and the amount of washing agent, as long as it can be washed to neutrality. The present invention does not specifically limit the parameters of the cutting, and those skilled in the art can perform cutting according to actual needs. In the present invention, the drying temperature is preferably 80 to 110°C, and the time is preferably 8 to 10 hours; the drying is preferably carried out in an oven.

[0043] In the present invention, the length of the waste fibers is preferably 10 to 50 mm.

[0044] The present invention mixes silicate and acid solution, and performs hydrolysis to obtain silica sol.

[0045] In the present invention, the silicate preferably includes one or more of methyl orthosilicate, ethyl orthosilicate, isopropyl silicate and butyl silicate. In the present invention, the acid solution preferably includes aqueous hydrochloric acid, aqueous sulfuric acid, aqueous nitric acid or aqueous acetic acid, and more preferably aqueous nitric acid. In the present invention, the mass concentration of the acid solution is preferably 10 to 30%.

[0046] In the present invention, the hydrolysis temperature is preferably room temperature, the hydrolysis time is preferably 0.5 to 2 hours, and more preferably 1 hour; the hydrolysis is preferably carried out under stirring, and the stirring speed is preferably 500 to 600 r / min.

[0047] After obtaining the silica sol, the present invention mixes the silica sol with a soluble calcium salt to obtain a calcium silicate sol.

[0048] In the present invention, the soluble calcium salt preferably includes calcium nitrate. In the present invention, the soluble calcium salt is preferably used in the form of a soluble calcium salt aqueous solution, and the concentration of the soluble calcium salt aqueous solution is preferably 100 to 120 mol / L.

[0049] In the present invention, the molar ratio of the silica sol to the soluble calcium salt is preferably 1:1, calculated as silicate.

[0050] In the present invention, when the soluble calcium salt is preferably used in the form of a soluble calcium salt aqueous solution, the silica sol and the soluble calcium salt are preferably mixed in a manner of: adding the soluble calcium salt aqueous solution dropwise into the silica sol.

[0051] In the present invention, the temperature for mixing the silica sol and the soluble calcium salt is preferably room temperature, that is, no additional heating or cooling is required; the time is preferably 10 to 120 minutes; the time for mixing the silica sol and the soluble calcium salt is preferably counted from the time when the soluble calcium salt aqueous solution is added dropwise. In the present invention, the mixing is preferably carried out under stirring.

[0052] After obtaining the calcium silicate sol and waste fibers, the present invention immerses the waste fibers in the calcium silicate sol to obtain waste fibers coated with the calcium silicate sol.

[0053] In the present invention, the immersion time is 10 to 48 hours. In the present invention, the immersion temperature is preferably room temperature, that is, no additional heating or cooling is required.

[0054] After the impregnation, the present invention preferably further comprises sequentially performing suction filtration and drying. The present invention does not specifically limit the operation of the suction filtration, and the suction filtration parameters well known to those skilled in the art can be used. In the present invention, the drying temperature is preferably 60 to 80°C, more preferably 70°C; and the drying time is preferably 3 to 5 hours.

[0055] After obtaining the waste fibers coated with the calcium silicate sol, the present invention calcines the waste fibers coated with the calcium silicate sol to obtain wollastonite coated waste fibers.

[0056] In the present invention, the calcination temperature is preferably 500-800° C., more preferably 600-700° C.; the holding time is preferably 3-5 h, more preferably 4 h.

[0057] In the present invention, the calcination can grow needle-shaped wollastonite crystals on the surface of the waste fiber, thereby increasing the surface area of ​​the waste fiber and enhancing the bonding force with the resin.

[0058] After obtaining the wollastonite-coated waste fibers, the present invention uses a modifier to impregnate the wollastonite-coated waste fibers to obtain the modified waste fibers.

[0059] In the present invention, the modifier is preferably a lipophilic active agent, and the lipophilic modifier preferably includes one or more of a silane coupling agent, a phthalate coupling agent, an organosilicon, stearic acid and a phosphate ester, and is further preferably a silane coupling agent, an organosilicon or stearic acid. In the present invention, the silane coupling agent preferably includes one or more of vinyl triethoxysilane, vinyl trimethoxysilane and polyether-modified polydimethylsiloxane. In the present invention, the organosilicon is preferably a polyether-type organosilicon.

[0060] In the present invention, the mass of the modifying agent is preferably 1 to 3% of the mass of the waste fibers, more preferably 1.2 to 2.5%, and even more preferably 1.5 to 2%.

[0061] In the present invention, the soaking temperature is preferably 20 to 80° C., and the soaking time is preferably 3 to 8 hours.

[0062] After the impregnation, the present invention preferably further comprises drying; the drying temperature is preferably 60 to 105° C., and the drying time is preferably 2 to 5 hours.

[0063] In the present invention, during the impregnation process, the modifier is bonded to the wollastonite coated waste fiber through hydrogen bonds and chemical bonds; and the composite with the modifier improves the compatibility of the modified waste fiber and the resin adhesive, thereby improving the tensile strength of the resin composite material.

[0064] The present invention also provides modified waste fibers obtained by the preparation method described in the above technical solution. In the present invention, the modified waste fibers include a waste fiber body, a wollastonite layer coated on the waste fiber body, and a modifier layer coated on the wollastonite layer.

[0065] The present invention also provides a molding compound, comprising resin, fiber and calcium carbonate;

[0066] The mass ratio of the resin, fiber and calcium carbonate is 100:20-35:70-80;

[0067] The fiber is the modified waste fiber described in the above technical solution.

[0068] The molding compound provided by the present invention comprises resin, and the resin preferably comprises one or more of unsaturated polyester, vinyl ester resin, epoxy resin, cyanate ester resin and phenolic resin.

[0069] The molding compound provided by the present invention comprises fibers, and the fibers are the modified waste fibers described in the above technical solution.

[0070] The molding compound provided by the present invention comprises calcium carbonate; the particle size of the calcium carbonate is preferably 800-3000 meshes.

[0071] In the present invention, the mass ratio of the resin, the fiber and the calcium carbonate is 100:20-35:70-80.

[0072] In the present invention, the method for preparing the molding compound preferably comprises the following steps:

[0073] The resin, fiber and calcium carbonate are mixed to obtain the molding compound.

[0074] The present invention does not specifically limit the manner of mixing the resin, fiber and calcium carbonate, as long as the three substances can be mixed uniformly.

[0075] The present invention also provides a fiber-reinforced resin-based composite material, which is obtained by arranging the molding compound described in the above technical solution layer by layer and then curing it.

[0076] The present invention has no requirements on the arrangement method and number of the molding compound layers, and those skilled in the art can arrange them according to actual needs.

[0077] In the present invention, the curing temperature is preferably 20 to 170° C., the pressure is preferably 10 to 20 MPa, and the curing time is preferably 2 to 8 hours.

[0078] The modified waste fiber and its preparation method and application provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0079] Example 1

[0080] The waste copper clad laminate is soaked in concentrated nitric acid with a concentration of 12 mol / L for 24 hours. Under the action of strong acid, the copper foil and the cured resin in the waste copper clad laminate are dissolved to obtain loose fibers. The loose fibers are washed with water until they are neutral, and then cut with a machine to form filamentous fibers with a length of 40 to 50 mm. The fibers are then placed in an oven at 110°C and dried for 8 hours to obtain waste fibers for standby use.

[0081] A nitric acid aqueous solution with a mass concentration of 30% was added to the tetraethyl orthosilicate, and the mixture was stirred at a speed of 600r / min for 1h to hydrolyze the tetraethyl orthosilicate to obtain silica sol. A calcium nitrate aqueous solution with a concentration of 100mol / L was added dropwise to the silica sol (the molar ratio of silica sol to calcium nitrate was 1:1 based on tetraethyl orthosilicate), and stirred for 10min after the addition to obtain calcium silicate sol; the waste fiber was immersed in the calcium silicate sol for 24h, filtered and placed in an oven, and dried at 70℃ for 5h to obtain waste fiber coated with calcium silicate sol; then the waste fiber coated with calcium silicate sol was placed in a muffle furnace and calcined at 600℃ for 4h to obtain wollastonite-coated waste fiber; the wollastonite-coated waste fiber was soaked with a silane coupling agent (the mass of the vinyl triethoxysilane coupling agent was 1.2% of the mass of the waste fiber) at 50℃ for 3h, and dried at 70℃ for 5h to obtain modified waste fiber.

[0082] Unsaturated polyester resin: modified waste fiber: calcium carbonate (particle size of 3000 mesh) are mixed in a mass ratio of 100:30:80 to obtain an SMC material with a thickness of 0.7 mm; the SMC material is cut into the same size as the flat mold, 3 layers are laid on the flat mold, and after the mold is closed, it is cured at 70°C and 10MPa for 2 hours to obtain a fiber-reinforced resin-based composite material.

[0083] The tensile strength of the obtained fiber-reinforced resin-based composite material measured by GB / T 1447-2005 standard is 33MPa, which is higher than the tensile strength of glass fiber-reinforced resin-based composite material (30MPa), and the cost of using waste fibers is greatly reduced.

[0084] Example 2

[0085] The waste copper clad laminate is soaked in concentrated nitric acid with a concentration of 12 mol / L for 24 hours. Under the action of strong acid, the copper foil and cured resin in the waste copper clad laminate are dissolved to obtain loose fibers. The loose fibers are washed with water until they are neutral, and then cut with a machine into filamentous fibers with a length of 40 to 50 mm. The fibers are then placed in an oven at 110°C and dried for 8 hours to obtain waste fibers for standby use.

[0086] Add 30% nitric acid aqueous solution to methyl orthosilicate, stir at 600r / min for 1h to hydrolyze methyl orthosilicate to obtain silica sol. Add 100mol / L calcium nitrate aqueous solution drop by drop to silica sol (the molar ratio of silica sol to calcium nitrate is 1:1 based on methyl orthosilicate), stir for 10min after adding, and obtain calcium silicate sol; soak waste fiber in calcium silicate sol for 48h, put into oven after filtration, and dry at 70℃ for 5h to obtain waste fiber coated with calcium silicate sol; then put waste fiber coated with calcium silicate sol into muffle furnace, calcine at 600℃ for 4h to obtain wollastonite coated waste fiber; soak wollastonite coated waste fiber with stearic acid (the mass of stearic acid is 1.8% of the mass of waste fiber) at 80℃ for 3h, and dry at 70℃ for 5h to obtain modified waste fiber.

[0087] Unsaturated polyester resin: modified waste fiber: calcium carbonate (particle size of 3000 mesh) are mixed in a mass ratio of 100:30:80 to obtain an SMC material with a thickness of 0.7 mm; the SMC material is cut into the same size as the flat mold, 3 layers are laid on the flat mold, and after the mold is closed, it is cured at 70°C and 10MPa for 2 hours to obtain a fiber-reinforced resin-based composite material.

[0088] The tensile strength of the obtained fiber reinforced resin matrix composite material was measured by GB / T 1447-2005 standard and was 34 MPa.

[0089] Example 3

[0090] The waste copper clad laminate is soaked in concentrated nitric acid with a concentration of 12 mol / L for 48 hours. Under the action of strong acid, the copper foil and cured resin in the waste copper clad laminate are dissolved to obtain loose fibers. The loose fibers are washed with water until they are neutral, and then cut with a machine to form filamentous fibers with a length of 40 to 50 mm. The fibers are then placed in an oven at 110°C and dried for 8 hours to obtain waste fibers for standby use.

[0091] A 30% nitric acid aqueous solution was added to butyl orthosilicate, and the mixture was stirred at a speed of 600 r / min for 1 hour to hydrolyze the butyl orthosilicate to obtain silica sol. A 100 mol / L calcium nitrate aqueous solution was added dropwise to the silica sol (the molar ratio of silica sol to calcium nitrate was 1:1 based on butyl orthosilicate), and the mixture was stirred for 10 minutes after the addition to obtain calcium silicate sol; the waste fiber was immersed in the calcium silicate sol for 24 hours, filtered, placed in an oven, and dried at 70°C for 5 hours to obtain waste fiber coated with calcium silicate sol; the waste fiber coated with calcium silicate sol was then placed in a muffle furnace and calcined at 600°C for 4 hours to obtain wollastonite-coated waste fiber; the wollastonite-coated waste fiber was impregnated with phosphate (the mass of the phosphate was 2.4% of the mass of the waste fiber) at 80°C for 4 hours, and dried at 70°C for 5 hours to obtain modified waste fiber.

[0092] Vinyl ester resin: modified waste fiber: calcium carbonate (particle size of 3000 mesh) are mixed in a mass ratio of 100:30:80 to obtain an SMC material with a thickness of 0.7 mm; the SMC material is cut into the same size as the flat mold, 3 layers are laid on the flat mold, and after the mold is closed, it is cured at 70°C and 10MPa for 3 hours to obtain a fiber-reinforced resin-based composite material.

[0093] The tensile strength of the obtained fiber-reinforced resin-based composite material measured by GB / T 1447-2005 standard is 36 MPa, which is 6 MPa higher than that of the glass fiber-reinforced resin composite material, and its oxygen index is increased from 16% to 28%.

[0094] Example 4

[0095] The waste copper clad laminate is soaked in concentrated nitric acid with a concentration of 12 mol / L for 48 hours. Under the action of strong acid, the copper foil and the cured resin in the waste copper clad laminate are dissolved to obtain loose fibers. The loose fibers are washed with water until they are neutral, and then cut with a machine to form filamentous fibers with a length of 40 to 50 mm. The fibers are then placed in an oven at 110°C and dried for 8 hours to obtain waste fibers for standby use.

[0096] A nitric acid aqueous solution with a mass concentration of 30% was added to the tetraethyl orthosilicate, and the mixture was stirred at a speed of 600r / min for 1h to hydrolyze the tetraethyl orthosilicate to obtain silica sol. A calcium nitrate aqueous solution with a concentration of 100mol / L was added dropwise to the silica sol (the molar ratio of silica sol to calcium nitrate was 1:1 based on tetraethyl orthosilicate), and stirred for 10min after the addition to obtain calcium silicate sol; the waste fiber was immersed in the calcium silicate sol for 48h, filtered and placed in an oven, and dried at 70℃ for 5h to obtain waste fiber coated with calcium silicate sol; then the waste fiber coated with calcium silicate sol was placed in a muffle furnace and calcined at 600℃ for 4h to obtain wollastonite-coated waste fiber; the wollastonite-coated waste fiber was impregnated with polyether-type silicone (the mass of polyether-type silicone was 3% of the mass of the waste fiber) at room temperature for 8h, and dried at 70℃ for 4h to obtain modified waste fiber.

[0097] Unsaturated polyester resin: modified waste fiber: calcium carbonate (particle size of 3000 mesh) are mixed in a mass ratio of 100:30:80 to obtain an SMC material with a thickness of 0.7 mm; the SMC material is cut into the same size as the flat mold, 3 layers are laid on the flat mold, and after the mold is closed, it is cured at 70°C and 10MPa for 2 hours to obtain a fiber-reinforced resin-based composite material.

[0098] The tensile strength of the obtained fiber reinforced resin matrix composite material was measured by GB / T 1447-2005 standard and was 35 MPa.

[0099] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing modified waste fiber, characterized in that: The following steps are involved: The waste copper clad laminate is immersed in a corrosive solution to dissolve the waste copper clad laminate to obtain waste fibers; Mixing silicate and acid solution, and hydrolyzing them to obtain silica sol; mixing the silica sol and a soluble calcium salt to obtain a calcium silicate sol; impregnating the waste fiber in the calcium silicate sol to obtain waste fiber coated with the calcium silicate sol; calcining the waste fiber coated with the calcium silicate sol to obtain wollastonite coated waste fiber; impregnating the wollastonite-coated waste fiber with a modifier to obtain the modified waste fiber; The etching solution includes one or more of concentrated sulfuric acid, concentrated nitric acid, concentrated hydrochloric acid, hydrofluoric acid and concentrated phosphoric acid.

2. The preparation method according to claim 1, characterized in that: The silicate comprises one or more of methyl orthosilicate, ethyl orthosilicate, isopropyl silicate and butyl silicate; The acid solution includes hydrochloric acid aqueous solution, sulfuric acid aqueous solution, nitric acid aqueous solution or acetic acid aqueous solution; the mass concentration of the acid solution is 10-30%.

3. The preparation method according to claim 1, characterized in that: The molar ratio of the silica sol to the soluble calcium salt is 1:1 based on silicate; the silica sol and the soluble calcium salt are mixed at room temperature for 10 to 120 minutes.

4. The preparation method according to claim 1, characterized in that: The immersion time is 10 to 48 hours.

5. The preparation method according to claim 1, characterized in that: The calcination temperature is 500-800° C., and the heat preservation time is 3-5 hours.

6. The preparation method according to claim 1, characterized in that: The modifier is a lipophilic active agent, and the lipophilic modifier includes one or more of a silane coupling agent, a phthalate coupling agent, organic silicon, stearic acid and a phosphate ester.

7. The preparation method according to claim 1 or 6, characterized in that: The mass of the modifier is 1-3% of the mass of the waste fiber; the soaking temperature is 20-80° C., and the soaking time is 3-8 hours.

8. The modified waste fiber obtained by the preparation method according to any one of claims 1 to 7.

9. A molding compound, characterized in that: Includes resins, fibers and calcium carbonate; The mass ratio of the resin, fiber and calcium carbonate is 100:20-35:70-80; The fiber is the modified waste fiber according to claim 8.

10. A fiber-reinforced resin-based composite material, characterized in that: The molding compound according to claim 9 is arranged layer by layer and then cured.

Citation Information

Patent Citations

  • Method for recycling waste fiber glass fabrics for glass production

    CN107311453A

  • Heatproof PVC wood-plastic decorative plate with low shrinkage rate and preparation method thereof

    CN110845808A